Marrakech Action Plan for Statistics, Partnership in Statistics for Development in the 21st Century, and Trust Fund for Statistical Capacity Building - Independent Evaluation Group (World Bank, Washington, DC, 2017)
This is the Global Program Review (GPR) of three related global partnership programs that aim to develop statistical capacity in developing countries the Marrakech Action Plan for Statistics (MAPS), the Partnership in Statistics for Development in the 21st Century (PARIS21), and the Trust Fund for Statistical Capacity Building (TFSCB). The three programs have been reviewed together in a single GPR because they have similar objectives, because the World Bank has been heavily involved in all three programs, and because of the potential to learn cross-cutting lessons of experience in relation to statistical capacity building (SCB). This GPR has also reviewed relevant internal materials (progress reports, results frameworks, minutes of governing body meetings, etc.) and other information available on the web. In addition, IEG has independently obtained opinions and views on the three programs by interviewing staff of the Bank and the PARIS21 Secretariat, and selected members of the PARIS21 Board at the 2010 Board meeting in Paris, France. This Independent Evaluation Group (IEG) review has identified a number of weaknesses in the external evaluations. First, while all three external evaluations clearly state that the assessment of program effectiveness was in their terms of reference, the focus was predominantly on processes and activities, with insufficient emphasis given to outputs and outcomes. While this may be justified by technical and conceptual challenges, the evaluations could have identified concrete ways in which the programs have contributed to the improvement in statistics and statistical capacity. Second, while all three evaluations share the common concern on the inadequate implementation of National Strategy for the Development of Statistics (NSDSs), they did not provide useful insights on how or to what extent NSDSs have helped with the development of national visions for statistical development. Third, there could have been a sharper focus and more specific recommendations on the notable lack of progress in the use of statistics in sub-Saharan Africa. Lastly, it would have been useful to have more systematic cross-references to the results of the analyses in the three evaluations.